Intellectual property law and the fourth industrial revolution - Heath, Christopher; Kamperman Sanders, Anselm; Moerland, Anke, 1983- (International intellectual property law series ;, 2020)
Intellectual Property Law and the Fourth Industrial Revolution' analyses how the fourth industrial revolution changes the framework of intellectual property rights in the context of data, competition and compliance and how these changes can serve society. It is in the very nature of intellectual property rights that their justification and scope correlate with extraneous factors, such as societal perception and technological development. The convergence of various fields of technology is changing the fabric of society. Big data and data mining, Internet of Things, artificial intelligence and blockchains are already affecting business models and leading to social and economic transformations that have been dubbed by the fourth industrial revolution.